Human-capital investment and the wage gap - Jürgen Meckl; Stefan Zink (Universität Konstanz, Fachbereich Wirtschaftswissenschaften, 2000)
According to empirical studies, the relation between the relative wage of skilled workers and their relative supply is U-shaped. This finding is explained by the effect of technological change on the incentives for humancapital investments made by heterogeneous individuals.
Keywords: I21; J31; 330; Wage inequality; human-capital investment